Association of eNOS 27-bp VNTR, 894G>T and 786T>C polymorphisms with susceptibility to Legg-Calve-Perthes Disease in Iranian children - Azarpira, Mohammad Reza (J Orthop, 2019)
BACKGROUND: The aim of this study was to analyze the association of eNOS polymorphisms with risk of Legg-Calve-Perthes Disease (LCPD). METHODS: The study comprised of 45 LCPD patients and 55 controls. The eNOS polymorphisms were genotyped with PCR and by PCR-RFLP. RESULTS: The eNOS 894G > T and −786T > C polymorphisms were significantly associated with an increased risk of LCPD. However, there was no significant association between eNOS 27-bp VNTR polymorphism and LCPD risk. CONCLUSION: Our results suggest that the eNOS 894G > T and −786T > C polymorphisms may be a risk factor for LCPD in Iranian children, but not 27-bp VNTR polymorphism.